PROPHETIC LEARNING IN ELT - AGUS HUSEIN AS SABIQ (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2018)
Affective teaching is substantive in the process of learning. It aims at developing excellent moral output. For Muslims, the Prophet Muhammad becomes the trendsetter in all aspects of their life. By examining some hadiths, the Prophet Muhammad did not only provide a form of that was only cognitive or afective, but in several conditions the prophet also gave an example of how to learn and teach. Therefore prophetic learning is necessarily integrated into all instructional contents so students can fully develop their attitude accordingly. English is a necessary subject, but on the other hand, it also teaches the idea of secularity which exist in English culture. Integrating prophetic learning in English language teaching can be done through: (1) teacher as a model; (2) stimulus response/questioning; (3) story telling; (4) analogy/logical order; (5) direct practice; (6) applied materials; (7) giving advice; (8) closing statement.